Overcoming challenges to deliver agricultural weather-index insurance - Erena, Getaneh; Popova, Viktoria; Vakaki, Eleni; Woerd, Joost van der; Zewdie, Yihenew (Technical Centre for Agricultural and Rural Cooperation, 2019)
This brief identifies and addresses key issues facing weather-index-based agricultural insurance. Drawing on diverse experiences from Africa and Central America, it zooms in on key challenges such as affordability, quality of weather data and models, raising awareness and trust in the benefits of insurance products and policy and regulatory frameworks. To have real impact, scale is the first requirement. Scaling strategies require reliable products, access to the rural areas, increased awareness about insurance and cost-effective delivery channels.